Biodegradation of volatile solids and water mass balance of bio-drying sewage sludge after electro-dewatering pretreatment. (15th May 2019) - Li, Qian; Zhi, Suli; Yu, Xiaoyan; Li, Yingte; Guo, Haigang; Yang, Zengjun; Zhang, Shuting
Highlights: The biodegradation of bio-drying electro-dewatered sludge was studied. Six kinetic models were analyzed using four statistical indicators. A new kinetic model was proposed to simulate volatile solids biodegradation. The water mass balance of bio-drying electro-dewatered sludge was calculated. Abstract: Using pressurized electro-osmotic dewatering (PEOD) as the pretreatment process for sewage sludge (SS) bio-drying can improve the dewatering performance, but the kinetics of volatile solids biodegradation and the water mass balance are still unknown. These processes were first investigated in this study. Experiments were conducted with three different initial materials, which were composed of SS, bio-dried product and SS dewatered by PEOD (EDSS) as different mass ratios. Six kinetic models and a nonlinear regression method were used to estimate the kinetic parameters, and the models were analyzed using four statistical indicators. Satisfactory fitting of the proposed kinetic model to the experimental data was achieved. Through the water mass balance, the results showed that EDSS had the best dewatering performance for bio-drying. EDSS provided the most appropriate conditions for the bio-drying process; the highest correlation coefficient was 0.9291 and the total water removal rate was 51.13% in the bio-drying of all EDSS.